Can Completing a Mental Health Nursing Course Change Students' Attitudes?. (4th May 2017) - Hastings, Todd; Kroposki, Margaret; Williams, Gail
ABSTRACT: Nursing program graduates rarely choose mental health nursing as a career. A quasi-experimental study was conducted to examine attitudes of 310 nursing students towards persons with mental illness. Students completed surveys on the first and last days of their program's psychiatric mental health nursing course. The pre- and post-test survey analysis indicated that students improved their attitude, knowledge and preparedness to care for persons with mental illness. However, students maintained little interest in working as a mental health nurse. Modifications in mental health nursing courses could be made to improve students' interest in choosing a career in mental health nursing.